THU0428 On the incidence of gout flares in primary care: a retrospective cohort study. (15th June 2017) - Janssens, H; Janssen, M; Fransen, J; Flendrie, M
Abstract : Background: From rheumatologist point of view (secondary care) there is a serious concern about suboptimal treatment of gout patients in primary care with warnings for worse prognostic consequences. (1) Some refer even to a "state of suboptimal gout care" promoted by "substantial gaps between rheumatologists and primary care providers" in their approaches to gout care: (2) the strategy of "treating-to-target" (to lower serum uric acid (SUA) levels <0.36mmol/L) versus "treating-to-avoid-symptoms" (often without addressing hyperuricemia). (3) Most studies on gout care in the primary care setting checked patients for prescribed urate lowering treatment (ULT), SUA assessments or reached SUA target levels, omitting the major patient related clinical end point of gout, flare frequency. (4) Objectives: To quantify the occurrence of flares and the use of ULT, in primary care patients with gout, and to analyze patient characteristics related to low or high flare frequency. Methods: A retrospective cohort study (setting one Dutch primary care center with an integrated medical praxis and pharmacy). Electronic medical records of ca. 5800 enlisted patients were used to select all patients with gout, to analyze their ULT use, and to assess flare frequency in a 2-year time window (2014–2015). Flare was defined as each pharmacy delivery of an anti-inflammatory drug or pain killer linked to a morbidity code for gout. Associations were studied between high or low flare frequency and patient characteristics by univariate logistic regression. Results: Of 173 included patients (prevalence 3%; mean age 66.4 yr; 75.7% men) 38.7% used ULT persistently during the 2-year time-window. Median time after initial diagnosis was 8.0 yr (IQR 3.0–14.5). Mean total numbers of flares in two years was 2.7 (SD: 4.7), median 1.0 (IQR: 0.0–4.0). Of the patients not receiving ULT (n=106, 61.3%) 41.5% had never, 25.5% one or two, and 6.6% more than six flares during two years. No associations were found between patient characteristics (e.g. age, time after initial diagnosis, crystal diagnosis, ULT use, cardiovascular co-morbidity, diuretic use) to differentiate patients with "no-or-1-flare" and "2-or-more-flares" per two years. Conclusions: Occurrence of flares in this stringently observed primary care cohort of patients with gout was very low, even if most patients did not use prophylactic ULT. Only 6.6% of patients experienced >6 flares in two years. Patients, in particular those not using ULT and with a low flare frequency (the majority), may reflect individuals with a distinctive (moderate) disease activity. They probably do not fulfill the general accepted advancing course of gout with ongoing and increasing flare frequency, MSU deposition, tophus formation, and joint damage. Immediate lifelong ULT for them may not be automatically indicated. Our study shows that suboptimal gout management in the perception of rheumatologists (secondary care) does not lead to an abundant number of gout flares in primary care patients. This urges to caution when recommendations based upon secondary care guide lines are advised for primary care patients with gout. References: Doherty M, et al. Ann Rheum Dis 2012;71:1765–70. Dalbeth N, et al. Arthritis Rheumatol 2017;69:22–34. McLean RM, et al. Ann Intern Med 2017;166:73–4. Morillon MB, et al. BMJ Open 2016;6:e012026. Disclosure of Interest: None declared